The successful use of the nasopharyngeal airway in Pierre Robin sequence: an 11-year experience. Issue 4 (13th February 2012) - Abel, Francois; Bajaj, Yogesh; Wyatt, Michelle; Wallis, Colin
Abstract : Introduction: Pierre Robin sequence (PRS) is a congenital anomaly presenting with micrognathia, glossoptosis and a cleft palate. This study describes a decade's experience of the management of upper airway obstruction (UAO) in PRS patients with a nasopharyngeal airway (NPA). Methods: This study was conducted by paediatric respiratory and otolaryngology departments. Children with PRS referred with UAO were evaluated according to a standard protocol. Data collected included the degree of airway obstruction, method of airway management, polysomnography data before and after intervention, and longer term follow-up. Results: Data were collected on 104 PRS patients referred to us for airway assessment in 2000–2010. 64/104 were aged <4 weeks at referral. Airway symptoms were managed conservatively in 27 patients (25.9%), with an NPA in 63 (60.6%) and a tracheostomy in 14 (13.4%). The average duration of NPA use was 8 months (3 weeks to 27 months). Polysomnography results improved in all 63 patients with an NPA. Fourteen severely obstructed patients underwent a tracheostomy. 86.5% (90/104) of PRS patients were managed conservatively or with the help of an NPA. There were no NPA related complications. Conclusion: There is a spectrum of UAO in PRS. This study reports on long-term outcomes in 104 children with PRS and airway obstruction. In most children (86.5%), airway obstruction was managed by conservative measures or with an NPA for a few months. The natural history shows that with normal growth, airway compromise resolves without immediate surgical intervention as advocated by some practitioners. Few PRS children require a tracheostomy.